2018
DOI: 10.1021/acscatal.8b03401
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cytochrome P450-Catalyzed Oxidations

Abstract: Enzymes are complex biological catalysts and are critical to life. Most oxidations of chemicals are catalyzed by cytochrome P450 (P450, CYP) enzymes, which generally utilize mixed-function oxidase stoichiometry, utilizing pyridine nucleotides as electron donors: NAD(P)H + O2 + R → NAD(P)+ + RO + H2O (where R is a carbon substrate and RO is an oxidized product). The catalysis of oxidations is largely understood in the context of the heme iron-oxygen complex generally referred to as Compound I, formally FeO3+, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
193
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(200 citation statements)
references
References 183 publications
2
193
0
5
Order By: Relevance
“…Further thorough comparison revealed that this finding is mediated by a new electron transfer pathway, which is not the same as any reported mechanisms for P450s. 30 Subsequently, based on sequence alignments with other microbial P450s, we found that residue Leu340 of HmtS is different from other enzymes. Thus, HmtS-L340F mutant was constructed to show higher catalytic efficiency.…”
Section: Discussionmentioning
confidence: 93%
“…Further thorough comparison revealed that this finding is mediated by a new electron transfer pathway, which is not the same as any reported mechanisms for P450s. 30 Subsequently, based on sequence alignments with other microbial P450s, we found that residue Leu340 of HmtS is different from other enzymes. Thus, HmtS-L340F mutant was constructed to show higher catalytic efficiency.…”
Section: Discussionmentioning
confidence: 93%
“…The most well‐known and extensively studied oxygenases are the cytochrome (Cyt) P450‐dependent monooxygenases that catalyze, among other reactions, regio‐ and stereoselective hydroxylations of alkanes, alkenes and aromatic hydrocarbons. It has been estimated that around 95 % of all enzyme‐catalyzed oxidations reported in the literature involve Cyt P450s . Indeed, the steroid hydroxylations developed in the middle of the last century (see Section 1) involved catalysis by Cyt P450s.…”
Section: On the Horizon: Optimization Of Enzymatic Oxyfunctionalizatimentioning
confidence: 99%
“…oxidations reported in the literature involve Cyt P450s. [163] Indeed, the steroid hydroxylationsd eveloped in the middle of the last century( see Section 1) involved catalysis by Cyt P450s. The latter are multicomponent biocatalysts in which reducing equivalents are provided by NAD(P)H indirectly to the P450 through am ediator, which can be af lavin or ferredoxin (see Scheme 20).…”
Section: Cytochromep 450-dependent Monooxygenasesmentioning
confidence: 99%
“…[1,2] When progressing to late transition metals,t he occupancyo fp-antibonding metal do rbitals increases,a nd metal-oxo bonds become weaker and more reactive.T his culminates in the rich chemistry of iron-oxo compounds,s uch as heme (P450) [3][4][5] and non-heme iron enzymes [6,7] that inspired the development of important C À H oxidation catalysts. [1,2] When progressing to late transition metals,t he occupancyo fp-antibonding metal do rbitals increases,a nd metal-oxo bonds become weaker and more reactive.T his culminates in the rich chemistry of iron-oxo compounds,s uch as heme (P450) [3][4][5] and non-heme iron enzymes [6,7] that inspired the development of important C À H oxidation catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Theterminal oxo ligand is astrong p donor that can form metal-oxo triple bonds with early transition metals such as in VO 2+ or MoO 3+ . [1,2] When progressing to late transition metals,t he occupancyo fp-antibonding metal do rbitals increases,a nd metal-oxo bonds become weaker and more reactive.T his culminates in the rich chemistry of iron-oxo compounds,s uch as heme (P450) [3][4][5] and non-heme iron enzymes [6,7] that inspired the development of important C À H oxidation catalysts. [8][9][10] In contrast, metal-oxo complexes beyond Group 8a re rare and exist only in square-pyramidal, [11] trigonal-pyramidal, [12,13] and, importantly,s quare-planar [14] coordination geometries in which electrons occupy MÀ On on-bonding (or weakly p * -antibonding) do rbitals.S tabilization of metal-oxo complexes beyond Group 8h as also been achieved by coordination of oxygen to Lewis acids.…”
Section: Introductionmentioning
confidence: 99%